Can Attachment Behaviors Moderate the Influence of Conflict Styles on Relationship Quality?. Issue 4 (2nd October 2019) - Hee, Cameron W. H.; Sandberg, Jonathan G.; Yorgason, Jeremy B.; Miller, Richard B.
Abstract: The current study uses a sample of married couples (N = 1718) to investigate the relationship between conflict styles and relationship quality as moderated by attachment behaviors. Results indicated that husbands' and wives' conflict style is significantly associated with their own perception of relationship quality, with more extreme styles being associated with decreases in relationship quality. Wives' conflict style was a significant predictor of husbands' relationship quality. Attachment behaviors moderated the negative relationship between conflict style and relationship quality but only for women and only at the trend level. The clinical applications of these findings are discussed.